The Application of Content and Language Integrated Learning to Improve Students’ Achievements in Academic Vocabularies and Scientific Writing - Achmad Mukhlisin; Ari Purnawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aimed to improve students' achievement in academic vocabulary and scientific writing through the implementation of the Content and Language Integrated Learning (CLIL) approach and to identify the challenges encountered by students at SMA Terpadu Pondok Pesantren Nurul Huda during its implementation. CLIL was selected because it integrates content learning with language development, allowing students to acquire academic language while engaging in meaningful subject-related tasks. The study employed a Classroom Action Research (CAR) design consisting of two cycles involving planning, action, observation, and reflection. The participants were senior high school students with basic English communicative competence. Data were collected through tests, classroom observations, and interviews and analyzed using quantitative and qualitative approaches. The findings revealed a statistically significant improvement in students’ academic vocabulary mastery and scientific writing skills following the CLIL intervention. Mean scores increased from 60.5 in the pre-test to 71.7 in the progress test and 80.3 in the post-test, while the paired-samples t-test showed a significant difference between pre-test and post-test results (p < 0.05). Students also demonstrated greater confidence in using domain-specific vocabulary, organizing ideas, and constructing coherent scientific abstracts. Nevertheless, they continued to experience difficulties in comprehending more complex texts from Scopus-indexed journals due to limited vocabulary range and insufficient academic reading skills. The findings suggest that CLIL can serve as an effective pedagogical approach for English teachers seeking to strengthen students' academic literacy through integrated language and content instruction. Overall, this study contributes to EFL teaching by providing evidence that structured CLIL implementation can enhance academic vocabulary development and support students' early engagement with scientific writing practices.